COMPARISON OF EFFECTIVENESS OF TOPICAL NIFEDIPINE AND DILTIAZEM IN THE TREATMENT OF ANAL FISSURES - SADIA, .; NASEER , S; FAROOQI , A; ZULFIKAR , I; SAEED , S; SHAH , HH (Biological and Clinical Sciences Research Journal, 2024)
Anal fissure, a tear in the anal canal below the dentate line, is commonly managed pharmacologically as the primary approach, with surgery considered secondary. Objective: To compare the efficacy of topical nifedipine and diltiazem in the prompt resolution of pain and bleeding associated with anal fissure management. Methods: A prospective cohort study was conducted at Dr. Ruth K. M. Pfau Civil Hospital, Karachi, from June 2023 to November 2023. One hundred patients with anal fissures were randomly allocated into two groups: Group N (Nifedipine) and Group D (Diltiazem). Topical medication was administered until healing occurred. The visual analogue scale (VAS) assessed the patient's progress in terms of bleeding and pain. Side effects were monitored. Statistical analysis included an independent t-test for comparing VAS scores and a post-stratification chi-square test for associations between bleeding, side effects, and other variables. Results: At baseline, mean pain scores were 8.30±0.90 in group D and 7.78±1.29 in group N. At the first follow-up, mean pain scores were 5.58±1.34 in group D and 4.56±1.48 in group N, with a significant difference (p<0.001). Bleeding did not significantly decrease at the first follow-up but decreased significantly at the subsequent follow-ups in both groups. Side effects did not differ significantly between groups. Conclusion: Topical nifedipine is more effective than diltiazem for managing anal fissures in terms of pain reduction. However, both medications showed comparable efficacy in reducing bleeding, with no significant difference in side effects observed.